Association of Carotid Plaque Morphology and Glycemic and Lipid Parameters in the Northern Manhattan Study - Della-Morte, David; Dong, Chuanhui; Crisby, Milita; Gardener, Hannah; Cabral, Digna; Elkind, Mitchell S. V.; Gutierrez, Jose; Sacco, Ralph L.; Rundek, Tatjana (Frontiers in Cardiovascular Medicine, 2022)
Low Gray-Scale Median (GSM) index is an ultrasonographic parameter of soft, lipid rich plaque morphology that has been associated with stroke and cardiovascular disease (CVD). We sought to explore the contribution of the modifiable and not-modifiable cardiovascular risk factors (RFs) to vulnerable plaque morphology measured by the low GSM index. A total of 1,030 stroke-free community dwelling individuals with carotid plaques present (mean age, 71.8 ± 9.1; 58% women; 56% Hispanic, 20% Non-Hispanic Black, 22% Non-Hispanic White) were assessed for minimum GSM (min GSM) using high-resolution B-mode carotid ultrasound. Multiple linear regression models were used to evaluate the association between RFs and minGSM after adjusting for sociodemographic characteristics. Within an individual, median plaque number was 2 (IQR: 1–3) and mean plaque number 2.3 (SD: 1.4). Mean minGSM was 78.4 ± 28.7 (IQR: 56–96), 76.3 ± 28.8 in men and 80 ± 28.5 in women; 78.7 ± 29.3 in Hispanics participants, 78.5 ± 27.2 in Non-Hispanic Black participants, and 78.2 ± 29 in Non-Hispanic white participants. In multivariable adjusted model, male sex (β = −5.78, p = 0.007), obesity BMI (β = −6.92, p = 0.01), and greater levels of fasting glucose (β = −8.02, p = 0.02) and LDL dyslipidemia (β = −6.64, p = 0.005) were positively associated with lower minGSM, while presence of glucose lowering medication resulted in a significant inverse association (β = 7.68, p = 0.04). Interaction (with p for interaction <0.1) and stratification analyses showed that effect of age on minGSM was stronger in men (β = −0.44, p = 0.03) than in women (β = −0.20, p = 0.18), and in individuals not taking glucose lowering medication (β = −0.33, p = 0.009). Our study has demonstrated an important contribution of glycemic and lipid metabolism to vulnerable, low density or echolucent plaque morphology, especially among men and suggested that use of glucose lowering medication was associated with more fibrose-stable plaque phenotype (greater GSM). Further research is needed to evaluate effects of medical therapies in individuals with vulnerable, low density, non-stenotic carotid plaques and how these effects translate to prevention of cerebrovascular disease.